Clinical Characteristics of Patients with Tetralogy of Fallot who Underwent an Invasive Procedure for Arrhythmias - Adelmann de Lima, Barbara; Gallo da Silva, Antonio Carlos; Saffi, Marco Aurélio Lumertz; Fröemming Junior, Clóvis; Castilhos, Gabriela; Lapa Kruse , Marcelo; Glotz de Lima, Gustavo; Luz Leiria, Tiago Luiz (JOURNAL OF CARDIAC ARRHYTHMIAS, 2021)
Introduction: Tetralogy of Fallot (TOF) is a cyanotic congenital heart disease that has an incidence of sudden cardiac death of 0.2% per year, being arrhythmias the main cause of its occurrence. Objective: To compare characteristics of TOF patients referred for electrophysiological study (EPS) against those that were not (No-EPS). Method: Retrospective cohort with 215 patients (57.2% men; age = 29 ± 4) with corrected TOF (median of three years, ranging from 0.33 to 51) that underwent EPS between 2009-2020. The primary outcome was composed of death, implantable cardiac defibrillator (ICD) requirement and hospitalization. Results: Pre-syncope (EPS = 4.7%, No-EPS = 0%; p = 0.004), syncope (EPS = 7.1%, No-EPS = 1.7%; p = 0.056) and palpitations (EPS = 31%, No-EPS = 5.8%; p < 0.001) were symptoms that justified electrophysiological investigation. ICD was implanted in 24% of EPS and 0.6% of No-EPS (p=0.001). Twenty-six percent of the EPS group presented non-sustained ventricular tachycardia, while 0% in No-EPS (p = 0.012). The EPS group had more atrial fibrillation or atrial Flutter (35.7% vs. 6.9%; p < 0.001). The EPS patients had a wider QRS duration than the no-EPS group (171.12 ± 29.52 ms vs. 147 ± 29.77 ms; p < 0.001). Also, 26.2% of EPS performed ablation to correct macroreentrant atrial tachycardias. The incidence of primary outcome (death + ICD requirement + hospitalization) was higher in patients in the EPS group compared to the No-EPS group (p = 0.001). However, the total of seven deaths occurred during the clinical follow-up, but without differences between the groups (EPS = 4.7% vs. No-EPS = 2.8%; p = 0.480). Conclusion: EPS group had a profile of greater risk, more complex heart disease, and a greater occurrence of the primary outcome when compared to the No-EPS group.